Exploring students’ speaking anxiety in an EFL classroom - Fatimah Hidayahni Amin,; Nur Masthurah, (Technium Social Sciences Journal, 2023)
This research aimed to find out the types of students’ speaking anxiety and students’ strategies to cope with their speaking anxiety in an EFL classroom. This research was conducted using descriptive qualitative method. The data collected by using observation checklist, in-depth interview, and online questionnaire. The participants of this research were students of first, third, and fifth semesters in Business English Communication program, Universitas Negeri Makassar. Based on the results of this research, it was found that there are more students who experience state anxiety and situation-specific anxiety than trait anxiety, as the type of anxiety that occurs when speaking English as a foreign language. Moreover, it was found that most students in the first, third, and fifth semesters used various techniques in doing preparation, relaxation, positive thinking, and seeking a peer as strategies to cope with speaking anxiety.